Progeny coriander resistant root-knot nematode - Santos, Ana Maria Maciel dos; Costa, Kleyton Danilo da Silva; Oliveira, Tâmara Rebecca Albuquerque; Silva, José Wilson da; Souza, Ênio Gomes Flôr; Carvalho Filho, José Luiz Sandes de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Coriander is a important vegetable crop in Brazil, being widely consumed as a condiment and cultivated mainly in North and Northeast brasilian regions. Diseases caused by Meloidogyne species are one main causers damages of crop. In the literature there is no reported about identification nematoid resistant coriander genotypes. In this study was carried the reaction evaluation of a heat-tolerant coriander population regarding resistance to Meloidogyne incognita race 1. Forty-six progenies of half-sibs were evaluated in a randomized block design, with three replications, the plot consisting of six plants. After 15 days of sowing the plants were inoculated using 1500 eggs of pathogen per plant. Evaluation occurred 45 days after inoculation, where evaluated characteristics were galls incidence, number of galls in washed root system and number of eggs per plant. Excepting incidence of galls, all variables presented significant difference by the F test, allowing the selection of 31 progenies according to the scale proposed by Oostenbrink. Phenotypic and genetic correlations between number of galls in root system and number of eggs were significant.